Maybe adaptive (not adaptable) automation in production: an experimental study comparing the locus of authority in work system dynamics - Berretta, Sophie; Tausch, Alina; Glogowski, Paul (Frontiers in Organizational Psychology, 2025)
IntroductionIn collaborative industrial work systems, the locus of authority—whether control over system dynamics is initiated by the system (adaptive) or by the human operator (adaptable)—can shape work experience and perceptions of the robotic partner. This study exploratively investigates how these control schemes and a static work system influence key psychological factors and which one should be favored in collaborative assembly tasks.MethodsIn an experimental laboratory study with n = 27 participants, a collaborative gearbox assembly task with a robot is used to compare adaptive and adaptable control schemes against a non-adjustable baseline. In the adaptive condition, the robot's speed automatically adjusted to human proximity; in the adaptable condition, speed is manually adjustable via interface buttons; in the baseline condition, speed remains static. The primary endpoint was the longitudinal, comparative investigation of flow experience and perceived task demands as they represent central indicators of employees' psychological experience in dynamic work systems. Dependent variables included additionally autonomy perception and workplace fit (task perception), and trust, safety, robot's intelligence, and collaboration satisfaction (robot interaction perception), as well as cycle time (performance), measured across four collaborative trials and five time points, making group comparisons and the investigation of construct dynamics possible.ResultsBoth control schemes demonstrated improved collaboration experiences compared to the baseline condition. Participants in the adaptive condition reported higher flow experience and workplace fit, and showed the fastest production times across all trials, while participants in the adaptable condition reported higher autonomy and task demands. Additionally, trust in the robot increases over time, harmonizing trust levels across conditions.DiscussionDespite limitations related to an exploratory design and a small sample size potentially masking existing effects, the findings indicate that dynamic working conditions can improve worker experience. However, the findings do not present a consistent picture favoring either adaptive or adaptable control schemes. Further research is needed to determine which control scheme is preferable in different task contexts. To inspire future work, we derive a set of hypotheses from the study's initial findings.